Cobalt-Free Core-Shell Structure with High Specific Capacity and Long Cycle Life as an Alternative to Li[Ni0.8Mn0.1Co0.1]O2. Issue 12 (3rd September 2020) - Liu, Yulong; Wu, Haohan; Li, Kui; Li, Hongyang; Ouyang, Dongxu; Arab, Phillip Peter; Phattharasupakun, Nutthaphon; Rathore, Divya; Johnson, Michel; Wang, Yiqiao; Yin, Shuo; Dahn, J. R.
Abstract : Reduction of the Co content in Ni-rich positive electrode materials is an intense research area of great interest. Despite high specific capacity, Co-free Ni-rich materials normally suffer from poor cycling performance. In this work, a Co-free precursor with a 16 μ m Ni(OH)2 core and 1 μ m Ni0.8 Mn0.2 (OH)2 shell was reacted with LiOH · H2 O at 750 °C (CS-750) or 800 °C (CS-800). CS-750 was found to retain the well-defined core–shell structure after heating, while CS-800 became homogeneous in composition due to Ni/Mn interdiffusion at the higher temperature. Although both of materials exhibit higher specific capacity than LiNi0.8 Mn0.1 Co0.1 O2 (NMC811) the charge-discharge capacity retention shows a dramatic difference. The cycling performance of CS-750 is equivalent to NMC811 samples, whereas CS-800 experiences significant capacity fade, suggesting the importance of a core–shell structure for Ni-rich materials with no Co. The electrical resistivity of CS-750 and CS-800 materials are comparable to NCA and are slightly lower than single crystal NMC811 suggesting that Co may not be essential to maintain good electrical properties. The authors believe CS-750 and related materials represent excellent Co-free options for high energy density Li-ion cells.